2017
DOI: 10.1142/s0219519417500300
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Differences in Lumbopelvic and Hip Movement Patterns During a Lower Limb Movement Test Between Two Groups of People With Low Back Pain

Abstract: Increased lumbopelvic motion during limb movements' tests was reported in low back pain (LBP) patients with and without rotational demand activities. The aim of this study was to compare lumbopelvic movement pattern between two groups of LBP patients with and without rotational demand activity during active hip external rotation test. Thirty nine patients with non-specific chronic LBP participated in this study. Patients were allocated into two groups, in first group 15 subjects (mean age ¼ 31:5 years) with ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Recently, some authors believe that subclassifying patients with LBP in homogeneous subgroups could considerably help in solving the problem ( 3 - 5 ). Differences in movement patterns of lumbopelvic of subgrouped people with LBP were also indicated in previous studies ( 4 , 6 - 9 ). Therefore, some authors have proposed models for the subgrouping of patients with LBP.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recently, some authors believe that subclassifying patients with LBP in homogeneous subgroups could considerably help in solving the problem ( 3 - 5 ). Differences in movement patterns of lumbopelvic of subgrouped people with LBP were also indicated in previous studies ( 4 , 6 - 9 ). Therefore, some authors have proposed models for the subgrouping of patients with LBP.…”
Section: Introductionsupporting
confidence: 80%
“…The obtained results can clarify how limb rotation may be related to LBP in patients with lumbar F + R syndrome. Some authors have suggested that increased lumbopelvic motion in a specific direction is a result of increased flexibility of the lumbopelvic soft tissues in those directions, which is induced by repeated movement of lumbopelvic motion in such directions through habitual or functional activities ( 4 , 28 , 30 ). Sadeghisani et al also demonstrated that forming of pattern of lumbopelvic movement impairment is a task-related sequence ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, external hip rotation ROM of the dominant limb was significantly increased in individuals who participated in rotational activities at least twice a week. 33 Limitations in either lumbar or pelvic regions caused the other region to compensate through abnormal motion, 31 predisposing individuals to injury.…”
Section: Lower Back Disordersmentioning
confidence: 99%
“… 19 , 42 , 70 If golfers rotate past functional limitations during the swing, the spinal vertebrae and the tendons and ligaments connecting the musculature around the vertebrae are stressed leading to a higher risk of injury. 33 Further research is needed to elucidate the relationship between LBP and hip mobility.…”
Section: Mechanisms Of Injury: Low Back Painmentioning
confidence: 99%